Impact of organic and inorganic carbon on the formation of nitrite during the VUV photolysis of nitrate containing water. (1st January 2020) - Han, Mengqi; Mohseni, Madjid
Abstract: Nitrite formation during Vacuum UV (VUV) photolysis of nitrate-containing water has been studied in this research. Here the goal was to understand the effect of water matrix, specifically dissolved organic carbon (DOC), dissolved inorganic carbon (DIC) and dissolved oxygen (DO), on the formation of nitrite in nitrate-containing water during treatment with VUV AOP. The results confirmed that the formation of nitrite was considerable during the VUV irradiation, and it increased with increasing the UV fluence. However, the rate of nitrite formation was not linearly correlated with the UV fluence. Also, nitrite formation increased with increasing the DOC in water. Tert-butanol, as OH radical scavenger, was used to elucidate the mechanism behind the impact of DOC. The effect of DIC was only pronounced at very high DIC concentration, which led to lower formation of nitrite. When both DOC and DIC were present in water, DOC had the dominant effect on nitrite formation. DO in water had the impact of reducing the formation of nitrite. All these results can help to understand the mechanisms involved in the transformation of nitrate to nitrite in various water matrices, and guide VUV applications for scientific and industrial proposes. Graphical abstract: Image 1 Highlights: Formation of nitrite under Vacuum UV radiation increases initially with UV fluence. Nitrite formation is correlated with relative concentrations of nitrate and nitrite. Dissolved organic carbon increases nitrite formation by scavenging OH radical. Dissolved inorganic carbon only affects nitrite formation at very high concentration. The air saturated water can help decrease nitrite formation.